Рolis platform «society and spiritual integrity of the people» of Al-Farabi (Journal of Philosophy Culture and Political Science, 2015)
In this article the political and ideogemny analysis on political-polisplatform «society and spiritual integrity of the people» based on the worksof Al-Farabi. The article made a political hermeneutic analysis on the aboveconcept of Al-Farabi on the basis of the factual background of ontogenesis.Determining the position of a political thinker revealed the social essence.
Keywords: аl-Farabi; society; a man spiritual integrity; оntogenesis.